(untitled) (Fiep Bulletin - online, 2014)
ABSTRACT. The goal of the study was to inventory the academic production in the Brazilian Physical Education of gender studies. The methodology included the rise of developed researches in the Graduation Programs Stricto Sensu. Therefore it was necessary to consult the databases of NUTESES-UFU; SIBRADID-UFMG and Plataforma LATTES, complemented with consulting the sector libraries of the programs. Sixty nine defended jobs were studied from 1984 to 2006. The mapping pointed to 17 institutions that gave origin to the studies and the greater part of these, located in the southeast region. The responsibility of the authorship and orientation is centered on the female sex. The subject with greater indicative worry of the researches was "gender and physical activities between girls and boys" and "woman, gender and sports". It was concluded that the need to extend the inventory, one time, that the database doesn’t suit the obtained information any other way.